Optimal condition determination for Flixweed standard seed germination test (Descurainia sophia) - Bita Oskouei; Abbas Dehshiri; Hadis Afshar; Elahe Gheysari; Ali Shayanfar (علوم و فناوری بذر ایران, 2023)
An experiment was implemented based on completely randomized design with four replications to determine standard Flixweed (Descurainia sophia) germination test condition. Flixweed seeds were placed in germinator for 14 days under 6 temperatures 10, 15, 20, 25, 20-30, 35ºC exposed to three treatments of potassium nitrate (2 grams per 1000 ml of distilled water), pre-chilling (7-10ºC for 7 days), pre-soaking (24h in distilled water), two cellulose substrates of top paper and between paper, and sands. Then, germination indexes were assessed. After comparison of three mentioned treatments (potassium nitrate, pre-chilling, and pre-soaking) with control it was demonstrated that the highest germination rate belonged to pre-chilling in 15ºC.The lowest amount of germination indices and the highest percentage of dead seeds were found in 25 and 35ºC. The best treatment to improve germination and seedling vigor was applying of potassium nitrate and optimal temperatures to reach maximum of germination was 10 and 15ºC. Higher germination was achieved when top and between paper substrate were used than sand. In total, it was suggested that it would be better for potassium nitrate to be under 10 and 15ºC when top and between paper and sand were applied, respectively to optimal condition for standard germination determination was achieved, because the highest percentage of final germination, normal seedlings, and seedling weight vigor, and also the lowest percentage of dead seeds were observed.